Promoting School Safety: A Comprehensive Emotional and Behavioral Health Model, Baltimore, Maryland, 2014-2017 - Lewis, April ([Verlag nicht ermittelbar], 2024)
Baltimore County Public Schools (BCPS) with funding from the U.S. Department of Justice, Office of Justice Programs, National Institute of Justice, Developing Knowledge about What Works to Make Schools Safe solicitation, partnered with The National Center for School Mental Health, University of Maryland to address the significant school safety issue of student emotional and behavioral health crises. In 2012, BCPS implemented a five-year strategic plan known as Blueprint 2.0: Our Way Forward. One of the major goals of the plan states: "Every school and office will be safe and secure, promote individual wellbeing and provide positive, respectful and caring environments for teaching, learning and working." The plan included key actions which call for "equitable access to counseling, social work, and psychological and other support services" as well as more "internal and external partnerships to improve delivery of mental health and other supportive services." This study employed a randomized controlled design to evaluate the impact of the emotional and behavioral health crisis response and prevention (EBH-CRP) model on school safety, emotional and behavioral health outcomes, and stakeholder knowledge and preparedness to address emotional and behavioral health concerns across the continuum. A cost-benefit analysis assessed the net benefits of the EBH-CRP intervention.